Potensi Metabolit Sekunder Tanaman Syzygium sp. Terhadap LOX-1 Sebagai Target Terapi Penyakit Aterosklerosis: Studi In Silico - Raizma, Elda Zaelita Nurul; Sopian, Devia Angelina; Alifianto, Handika Maulana; Eshananda, Yuriza; Simanjuntak, Sorta Basar Ida (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
Atherosclerosis is a cardiovascular disease characterized by the accumulation of oxidized lipoproteins in the arterial wall, which is triggered by LOX-1 receptor activation. The members of Syzygium genus contains secondary metabolites with antioxidant and anti-inflammatory activities that have the potential to inhibit LOX-1. This study aims to evaluate the interaction of compounds from Syzygium cumini, Syzygium aromaticum, Syzygium malaccense, and Syzygium jambos against LOX-1 using in silico method. Analysis was conducted through molecular docking, pharmacophore selection based on hydrophobic and hydrogen bond interaction criteria, and validation using Root Mean Square Deviation (RMSD â‰¤ 3 Ã…) values. The research results showed that gallic acid has the highest affinity (-4.1 kcal/mol), followed by linalool (-3.8 kcal/mol), kaempferol (-3.4 kcal/mol), oxalic acid (-3.4 kcal/mol), quercetin (-2.2 kcal/mol), and myricetin (-1.4 kcal/mol). The compounds with the highest affinity interacted with key LOX-1 residues, suggesting potential inhibition of the receptor. In conclusion, gallic acid is the most potent LOX-1 inhibitor candidate based on its stable interaction and highest affinity value. Further studies are needed to confirm its biological activity through in vitro and in vivo approaches.